Joaquin Chiriboga: A forgotten democrat - Chiriboga, Joaquin (Revista Universidad de Guayaquil, 1983)
There are many men upon whom our history has placed a heavy dam of silence and oblivion. And not because of a bad memory most of the time, but because powerful class interests have stood in the way of the truth, forcing historians to hide their knowledge on some occasions, to deepen their ignorance on some occasions. The same reasons, in other cases, have led to praising mediocrities and throwing incense at the feet of ridiculous tyrants. Such small despots, like Juan José Flores, for example. Joaquín Chiriboga, a former clergyman, is one of those forgotten men. Very little is known about his life.